To simplify the expression 4*6 • 4*-8, we perform the multiplications first.
4*6 = 24
4*-8 = -32
Therefore, the expression simplifies to 24 • -32.
Simplify the expression
4*6• 4*−8
5 answers
wrong;
Apologies for the mistake. Let's simplify the expression correctly.
4 * 6 = 24
4 * -8 = -32
Now, we have 24 * -32.
24 * -32 = -768
So, the final simplified expression is -768.
4 * 6 = 24
4 * -8 = -32
Now, we have 24 * -32.
24 * -32 = -768
So, the final simplified expression is -768.
Wrong
Apologies for the incorrect response. Let's simplify the expression correctly.
4*6 = 24
4*-8 = -32
Now, we have 24 * -32.
The product of a positive number (24) and a negative number (-32) is always negative.
So, the final simplified expression is -768.
4*6 = 24
4*-8 = -32
Now, we have 24 * -32.
The product of a positive number (24) and a negative number (-32) is always negative.
So, the final simplified expression is -768.